Mechanical and water absorption behaviors of corn stalk/sisal fiber‐reinforced hybrid composites. Issue 26 (8th March 2018) - Chen, Juan; Zou, Yu; Ge, Heyi; Cui, Zedong; Liu, Shanshan
ABSTRACT: In this study, corn stalk flour (CSF) was used as filler instead of wood flour (WF) to prepare poly(vinyl chloride) (PVC) based wood plastic composite (WPC). In order to enhance the mechanical properties of the WPC, sisal fiber (SF) was introduced as reinforcer. The mechanical and the water absorption behaviors of WPC were investigated in detail. The results indicated that the chemical structure of CSF proved by FTIR was similar to that of WF. The effect of the hybridization of SF and CSF on the mechanical and water absorption behaviors of CSF/SF/PVC composite was studied. It was found that the introduction of SF of 5 mm in length resulted in improvement of the mechanical properties and had little effect on water absorption behavior. Scanning electron microscopy was carried out to observe the fracture surface of the composite. The distribution of CSF and SF in PVC was analyzed. Meanwhile, the hybrid enhancement mechanism of SF in PVC matrix was discussed. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46405. Abstract :